Osteoporosis Recovery by Antrodia camphorata Alcohol Extracts through Bone Regeneration in SAMP8 Mice. (10th April 2016) - Liu, Hen-Yu; Huang, Chiung-Fang; Li, Chun-Hao; Tsai, Ching-Yu; Chen, Wei-Hong; Wei, Hong-Jian; Wang, Ming-Fu; Kuo, Yueh-Hsiung; Cheong, Mei-Leng; Deng, Win-Ping
Abstract : Antrodia camphorata has previously demonstrated the efficacy in treating cancer and anti-inflammation. In this study, we are the first to evaluate Antrodia camphorata alcohol extract (ACAE) for osteoporosis recovery in vitro with preosteoblast cells (MC3T3-E1) and in vivo with an osteoporosis mouse model established in our previous studies, ovariectomized senescence accelerated mice (OVX-SAMP8). Our results demonstrated that ACAE treatment was slightly cytotoxic to preosteoblast at 25 μ g/mL, by which the osteogenic gene expression (RUNX2, OPN, and OCN) was significantly upregulated with an increased ratio of OPG to RANKL, indicating maintenance of the bone matrix through inhibition of osteoclastic pathway. Additionally, evaluation by Alizarin Red S staining showed increased mineralization in ACAE-treated preosteoblasts. For in vivo study, our results indicated that ACAE inhibits bone loss and significantly increases percentage bone volume, trabecular bone number, and bone mineral density in OVX-SAMP8 mice treated with ACAE. Collectively, in vitro and in vivo results showed that ACAE could promote osteogenesis and prevent bone loss and should be considered an evidence-based complementary and alternative medicine for osteoporosis therapy through the maintenance of bone health.